AN ENHANCED MODEL FOR PREMIUM MOTOR SPIRIT (PMS) PRICE PREDICTION AND MANAGEMENT IN NIGERIA USING MACHINE LEARNING - Anazia, Kizito Eluemunor; Ojei, Emmanuel Obiajulu; Ekibade, O. Jahswill; Idama, Rebecca Okeoghene (FUDMA JOURNAL OF SCIENCES, 2024)
Forecasting Premium Motor Spirit (PMS) prices accurately is crucial for economic stability and effective decision-making in Nigeria. Premium Motor Spirit (PMS), which is also known as petrol or fuel, plays a pivotal role in the country's economy, impacting transportation costs, inflation rates, and overall economic growth. However, the unpredictability of PMS prices prediction and management is influenced by factors like government policies, international oil markets, supply chain disruptions, stakeholders and interested cartels amongst others. This has created a constant price fluctuation, poor price control and management which eventually lead to fuel scarcity and high cost of fuel. The price control mechanism remains a contentious issue, with debates over its impact on the economy, government spending, and the welfare of ordinary Nigerians. This article presents an enhanced model for Premium Motor Spirit (PMS) price prediction and management in Nigeria using machine learning that will improve the price prediction and management system that will produce high degree of accuracy. The system was developed using visual studio C#, ML.Net model and Microsoft SQL server for its backend database. This model identifies key factors impacting PMS prices prediction and management that is used to forecast PMS prices over a specified time horizon such as daily, weekly, or monthly thereby enhancing economic planning and stability in Nigeria.
Keywords: Premium Motor Spirit; Machine Learning; Price Prediction; Management